Kinetics of cinnamaldehyde hydrogenation in four phase system - Khan, M.; Joshi, S.; Ranade, V. (Chemical Engineering Journal, 2019)
The kinetics of cinnamaldehyde hydrogenation in four phase system viz. gas (hydrogen)-liquid (cinnamaldehyde + toluene)-liquid (aqueous KOH)-solid (catalyst, 5% Pt/C), [GLLS] system has been studied in this work. As reported, addition of aqueous alkali in hydrogenation of unsaturated aldehydes like cinnamaldehyde shifts selectivity towards unsaturated alcohol, cinnamyl alcohol. The promotion action by alkali metals for improving selectivity towards cinnamyl alcohol involves changes in the adsorption mechanism of the cinnamaldehyde in a way that CO bond get preferentially hydrogenated. In cinnamaldehyde hydrogenation in presence of promoters two different catalytic sites can be considered, each for CO and CC bond hydrogenation. In accordance with this consideration and as demonstrated in various studies on hydrogenation of unsaturated aldehydes, further hydrogenation of intermediate-cinnamyl alcohol (CC bond hydrogenation) occurs on Pt only sites while cinnamaldehyde and intermediate hydrocinnamaldehyde (both involving CO bond hydrogenation) are hydrogenated on catalytic sites affected by promoters. This preferential adsorption and hydrogenation through CO bond leads to the increased selectivity of cinnamyl alcohol. Although, many authors have studied cinnamaldehyde hydrogenation using various promoters, there are very few reports on kinetics in which this two site approach behind promotion action has been considered. The effect of various operating parameters on the rates of hydrogenation was studied and the two site Langmuir-Hinshelwood type of kinetic model was used for evaluating the kinetic parameters by fitting experimental data. The thermodynamic model for estimating the solubility of hydrogen in the reaction mixture was incorporated with this kinetic model.